Optimization of Tunisian Myrtus communis L. Essential Oil Extraction by Complete Factorial Experimental Design - Rania Zayani; Eya BenSalem; Mariem Khouja; Amani Bouhjar; Mohamed Boussaid; Chokri Messaoud (Metabolites, 2025)
Background: Myrtus communis L. is a typical aromatic species of the Mediterranean basin, whose leaves are rich in essential oil known for its biological properties. Methods: The essential oil of Tunisian Myrtus communis L. leaves was extracted via hydrodistillation using a Clevenger-type apparatus and optimized using a complete factorial design including three factors with two different modalities and one factor with three modalities, hence the total number of experiments Ntotal = 23 × 31. This optimization concerns the yield, the terpene composition by GC-MS and the antioxidant activity by the two radical scavenging assays, DPPH and ABTS. Four factors were retained, namely, the type of leaf used (dry or fresh sample), the leaf granulometry (whole or ground), the extraction time (1 h 30 min, 2 h 30 min and 3 h 30 min) and the water volume/plant material ratio (1/4 and 1/10). Results: The dry and whole leaves, duration 3 h 30 min, and V/M 1/10 modalities gave the best yield of essential oil (0.77%). The optimal contents of the majority of the terpene compounds, 1,8-cineole (37.23%), α-pinene (54.79%), myrtenyl acetate (23.43%) and limonene (17.77%), were recorded using the modalities dry and whole leaves, duration 2 h 30 min, V/M 1/10; dry and ground leaves, duration 1 h 30 min, V/M 1/4; fresh and whole leaves, duration 3 h 30 min, V/M 1/4; and fresh and whole leaves, duration 3 h 30 min, V/M 1/4, respectively. The antioxidant activity of the essential oil of myrtle leaves was optimized for the two DPPH (7.477 mg TE/g EO) with the GDL, duration 3 h 30 min, V/M 1/4 and ABTS assays (14.053 mg TE/g EO) with WDL terms, duration 3 h 30 min, V/M 1/10. Conclusions: Optimizing essential oil extraction is of significant interest to the cosmetic, perfumery, and pharmaceutical industries, which are constantly seeking optimal conditions to enhance essential oil yield and to ensure a high concentration of terpenic compounds, valued for their aromatic qualities and diverse biological activities.